Early Results of a Geriatric Hip Fracture Program in India for Femoral Neck Fracture. (March 2015) - Jain, Deepak; Sidhu, Guraziz Singh; Selhi, Harpal Singh; Mears, Simon C.; Yamin, Mohammad; Mahindra, Pankaj; Pannu, Harminder Singh
Geriatric hip fractures are a challenging clinical problem throughout the world. Hip fracture services have been shown to shorten time to surgery, decrease the cost of admissions, and improve the outcomes. We instituted a geriatric hip fracture program for comanagement of these injuries by orthopedic and internal medicine teams at our hospital in India. From January 2010 till December 2011, 119 patients with a femoral neck fracture were treated with cemented modular hemiarthroplasty under this program using a cost-effective Indian implant. The cohort included 63 males and 56 females with a mean age of 70.7 years (range 55-98 years). Hypertension (n = 42) and diabetes mellitus (n = 29) were the most common comorbidities. The follow-up period ranged from 12 to 37 months with an average of 24 months. The surgery was performed within 24 hours of admission in 60.5% (n = 72) patients. The use of antiplatelet drugs was the most common reason for delay of surgery. The mean length of hospital stay was 10.4 days (range 3-24 days) with 77% (n = 92) of patients discharged within 1 week of admission. On follow-up, good to excellent Harris hip scores were seen in 88% of patients with 76% of patients returning to the preinjury ambulatory status. The mortality rate was 6% at 6 months follow-up and 10.9% at 2 years. Our study shows that a hip fracture program can be instituted in India. The program helped us in achieving the goal of early surgery, mobilization, and discharge from hospital with decreased mortality.